Conversion training of conventional to sharia cooperatives for regional leaders of 'Aisyiyah, Malang City - Tinuk Dwi Cahyani; Rahayu Hartini; Fadilla Muhammad Mahdi (Community Empowerment, 2021)
Islamic Cooperation; Conversion; Training